2009
DOI: 10.1152/ajpgi.90622.2008
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-GEF cytoprotection by Src tyrosine kinase activation of phosphoinositide-3-kinase p110 β/α in rat hepatocytes

Abstract: Gates A, Hohenester S, Anwer MS, Webster CRL. cAMP-GEF cytoprotection by Src tyrosine kinase activation of phosphoinositide-3-kinase p110 ␤/␣ in rat hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 65 publications
2
31
1
Order By: Relevance
“…Such a hypothesis is consistent with the other findings that a) PI3K-Akt pathway is cytoprotective(Gates et al 2009, Rust et al 2005, Webster et al 2002b), b) the cytoprotective effect of cAMP-GEF in hepatocytes is associated with PI3Kp110α/p110β activation (Gates et al 2009), and c) PI3K-p110α is necessary for insulin signaling in the liver(Foukas et al 2006). …”
Section: Signaling Pathways Affected By Bile Acidssupporting
confidence: 91%
See 2 more Smart Citations
“…Such a hypothesis is consistent with the other findings that a) PI3K-Akt pathway is cytoprotective(Gates et al 2009, Rust et al 2005, Webster et al 2002b), b) the cytoprotective effect of cAMP-GEF in hepatocytes is associated with PI3Kp110α/p110β activation (Gates et al 2009), and c) PI3K-p110α is necessary for insulin signaling in the liver(Foukas et al 2006). …”
Section: Signaling Pathways Affected By Bile Acidssupporting
confidence: 91%
“…For example, activation ofp110α is implicated in cell survival (Benistant et al 2000, Gates et al 2009), physiologic cardiac hypertrophy (Pretorius et al 2009), and insulin signaling (Foukas et al 2006). De novo DNA synthesis (Benistant et al 2000) and carcinogenesis (Jia et al 2008) are associated with activation of p110β.…”
Section: Signaling Pathways Affected By Bile Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then various studies have provided evidence supporting a role for PI3K/Akt pathway in cell survival and translocation of hepatocellular transporters to the plasma membrane, indicating a beneficial role of PI3K in hepatic cells (4,48,130,160). PI3Ks are a family of lipid kinases (classes I, II, and III) that phosphorylate the inositol ring of phosphatidylinositides (PIs) at 3 position known as D3 phosphorylation (24).…”
Section: Post-translational Regulation Of Ntcp and Asbtmentioning
confidence: 99%
“…It has been reported that the cytoprotective effect of cAMP-GEF in hepatocytes is associated with PI3K p110α/p110β activation (Gates et al, 2009), and p110α is known to be necessary for insulin signaling in the liver (Foukas et al, 2006). Further, Hohenester and colleagues revealed that PI3K p110γ contributes to bile-salt induced apoptosis in hepatocytes (Hohenester et al, 2010).…”
Section: I3 Phosphatidyl-insitol-3-kinase (Pi3k)mentioning
confidence: 99%